PENGARUH KOMBINASI PAKAN AZOLLA PINNATA DAN PELLET KOMERSIAL TERHADAP PERTUMBUHAN BERAT DAN KELANGSUNGAN HIDUP IKAN NILA (Oreochromis niloticus) - Rustamaji, Bambang; Kusyairi, Achmad; Madyowati, Sri Oetami (Jurnal Perikanan Pantura (JPP), 2026)
Azolla pinnata has a fairly high protein content, which is around 25-35% dry weight, and is easy to cultivate on a large scale. The use of this plant as feed is expected to be a solution to reduce production costs. The purpose of this study was to determine the effect of adding natural feed Azolla pinnata and commercial pellet feed, on the weight growth and survival of tilapia (Oreochromis niloticus). The method used in this study was an experimental method with a Completely Randomized Design (CRD) then tabulated and used covariance analysis to determine the growth and survival of tilapia (Oreochromis niloticus). Consisting of 3 treatments with 9 replications: A (100% Pellet), B (50% Pellet, 50% Azolla pinnata), C (100% Azolla pinnata), with a density of 6 fish / 15 liters of water for 30 days. The results of the study showed that the combination treatment of Azolla pinnata and commercial pellets produced a higher average absolute weight growth rate than other treatments. The average absolute weight growth value of treatment B was 3.037 grams and the survival rate was 81.48%. The water quality of all treatments during the study showed a suitable range to support tilapia (Oreochromis niloticus) cultivation, namely the average temperature in treatment A was between 27.4545oC – 28.4545oC, treatment B was between 27.4545oC – 28.5455oC, treatment C was between 27.3636oC – 28.6364oC. For the average pH in treatment A was between 6.6818 – 7.3273, treatment B was between 6.6 – 7.1182 and treatment C was between 6.7273 – 7.1273. Meanwhile, the average Dissolved Oxygen (DO) for treatment A was between 6.2727 – 7.3636 ppm, for treatment B between 6.6364 – 7.2727 ppm, and for treatment C between 6.6364 – 7.0909 ppm. This research is not yet perfect and further research on Azolla pinnata is needed so that it can be used by cultivators effectively and efficiently.